Differential DNA methylation profile in infants born small-for-gestational-age: association with markers of adiposity and insulin resistance from birth to age 24 months - Abel López-Bermejo; Francis de Zegher; Lourdes Ibáñez; Marta Diaz; Edurne Garde (BMJ Open Diabetes Research & Care, 2020)
Introduction Prenatal growth restraint followed by rapid postnatal weight gain increases lifelong diabetes risk. Epigenetic dysregulation in critical windows could exert long-term effects on metabolism and confer such risk.Research design and methods We conducted a genome-wide DNA methylation profiling in peripheral blood from infants born appropriate-for-gestational-age (AGA, n=30) or small-for-gestational-age (SGA, n=21, with postnatal catch-up) at age 12 months, to identify new genes that may predispose to metabolic dysfunction. Candidate genes were validated by bisulfite pyrosequencing in the entire cohort. All infants were followed since birth; cord blood methylation profiling was previously reported. Endocrine-metabolic variables and body composition (dual-energy X-ray absorptiometry) were assessed at birth and at 12 and 24 months.Results GPR120 (cg14582356, cg01272400, cg23654127, cg03629447), NKX6.1 (cg22598426, cg07688460, cg17444738, cg12076463, cg10457539), CPT1A (cg14073497, cg00941258, cg12778395) and IGFBP 4 (cg15471812) genes were hypermethylated (GPR120, NKX6.1 were also hypermethylated in cord blood), whereas CHGA (cg13332653, cg15480367, cg05700406), FABP5 (cg00696973, cg10563714, cg16128701), CTRP1 (cg19231170, cg19472078, cg0164309, cg07162665, cg17758081, cg18996910, cg06709009), GAS6 (N/A), ONECUT1 (cg14217069, cg02061705, cg26158897, cg06657050, cg15446043) and SLC2A8 (cg20758474, cg19021975, cg11312566, cg12281690, cg04016166, cg03804985) genes were hypomethylated in SGA infants. These genes were related to β-cell development and function, inflammation, and glucose and lipid metabolism and associated with body mass index, body composition, and markers of insulin resistance at 12 and 24 months.Conclusion In conclusion, at 12 months, abnormal methylation of GPR120 and NKX6.1 persists and new epigenetic marks further involved in adipogenesis and energy homeostasis arise in SGA infants. These abnormalities may contribute to metabolic dysfunction and diabetes risk later in life.